(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Operation instead of screening method to solve the congruence equation. Discussion on the expression of prime numbers and its applications; Setting up the residual model to solve the problem of related distribution; The problem of solving the problems about prime pairs of even numbers with the correspondence model of even numbers.